Phrases figées illocutoires: quelle interprétation sémantique? - Náray-Szabó, Márton (Verbum – Analecta Neolatina, 2009)
Bound utterances like A votre santé!; Tu vois!; Ça va! are frequent reactions to more or less well-defined speech situations. Many of them bear idiomatic properties, even though linguists sometimes do not regard them as such. We first give an account on discourse acts from a lexicalist point of view, that is, in terms of argument structure. After that, we provide a full analysis on illocutionary frozen sentences based on the notion of illocutionary predicate. Parting from these theoretical considerations, we discuss the results of an investigation carried out on some 200 French expressions. Examined features are morphological, lexical and syntactical constraints. As a result, evidence is shown that idiomaticity in these utterances has properties that no other types possess.